2018
DOI: 10.3389/fmicb.2018.02611
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Signatures of Dairy Lactobacillus casei Group

Abstract: Lactobacillus casei/Lactobacillus paracasei group of species contains strains adapted to a wide range of environments, from dairy products to intestinal tract of animals and fermented vegetables. Understanding the gene acquisitions and losses that induced such different adaptations, implies a comparison between complete genomes, since evolutionary differences spread on the whole sequence. This study compared 12 complete genomes of L. casei/paracasei dairy-niche isolates and 7 genomes of L. casei/paracasei isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…(Al-Okbi and Mohamed, 2012;Lucatto et al, 2020). Lactobacillus casei is a gram-positive, mesophilic, microaerophilic, catalase-negative, and spore-free bacterium and a facultative hetero-formative bacterium with high acid production capacity (Fontana et al, 2018). L. casei is a probiotic strain linked with antihypertensive antioxidant, antihypocholesterolemic and anticarcinogenic, characteristics (Balthazar et al, 2018;Garcia et al, 2019).…”
Section: Preparation Of Inoculumsmentioning
confidence: 99%
“…(Al-Okbi and Mohamed, 2012;Lucatto et al, 2020). Lactobacillus casei is a gram-positive, mesophilic, microaerophilic, catalase-negative, and spore-free bacterium and a facultative hetero-formative bacterium with high acid production capacity (Fontana et al, 2018). L. casei is a probiotic strain linked with antihypertensive antioxidant, antihypocholesterolemic and anticarcinogenic, characteristics (Balthazar et al, 2018;Garcia et al, 2019).…”
Section: Preparation Of Inoculumsmentioning
confidence: 99%
“…The comparative analysis of genome sequences was carried out among all the S. thermophilus strains available in the public database. This kind of comparative phylogenetic analysis that is used for inspection of probiotic potentials has already been done for other bacterial species, such as Lactobacillus acidipiscis, Lactobacillus crispatus, Lactobacillus casei, and Lactobacillus helveticus (Ojala et al, 2014;Fontana et al, 2018Fontana et al, , 2019Kazou et al, 2018). Furthermore, important technological properties of the four strains were investigated including milk acidification, antibiotic resistance, EPS and γ-aminobutyric acid (GABA) production ability, and in vitro survival capacity in the gastrointestinal tract (GIT).…”
Section: Introductionmentioning
confidence: 99%
“…In our research, Bacillus pumilus , Bacillus amyloliquefaciens , Lactobacillus casei , and Lactococcus lactis contained strains that were not considered to be of the same species, and which were instead classified into two groups based on 95% ANI (Supplementary Figure S1). For example, when mapping a shotgun read simulated from the genome of the L. casei type strain (GCF_000019245.4) to a genome of L. casei (GCF_000829055.1) in another group, we found that the read mapping coverage was very low, to the extent that it cannot be regarded as the same species (Supplementary Figure S2; Fontana et al, 2018). Although L. casei did not have any officially named subspecies, the nine strains analyzed were divided in two groups consisting of seven and two strains, with the latter two strains being L. casei LC5 and L. casei ATCC 393.…”
Section: Resultsmentioning
confidence: 99%